Genome-wide association study detected novel susceptibility genes for social cognition impairment in people with schizophrenia. (2nd January 2022) - Gennarelli, Massimo; Monteleone, Palmiero; Minelli, Alessandra; Monteleone, Alessio Maria; Rossi, Alessandro; Rocca, Paola; Bertolino, Alessandro; Aguglia, Eugenio; Amore, Mario; Bellino, Silvio; Bellomo, Antonello; Biondi, Massimo; et al.
Abstract: Objectives: People with schizophrenia (SCZ) present serious and generalised deficits in social cognition (SC), which affect negatively patients' functioning and treatment outcomes. The genetic background of SC has been investigated in disorders other than SCZ providing weak and sparse results. Thus, our aim was to explore possible genetic correlates of SC dysfunctions in SCZ patients with a genome-wide study (GWAS) approach. Methods: We performed a GWAS meta-analysis of data coming from two cohorts made of 242 and 160 SCZ patients, respectively. SC was assessed with different tools in order to cover its different domains. Results: We found GWAS significant association between the TMEM74 gene and the patients' ability in social inference as assessed by The Awareness of Social Inference Test; this association was confirmed by both SNP-based analysis (lead SNP rs3019332 p -value = 5.24 × 10 −9 ) and gene-based analysis ( p -value = 1.09 × 10 −7 ). Moreover, suggestive associations of other genes with different dimensions of SC were also found. Conclusions: Our study shows for the first time GWAS significant or suggestive associations of some gene variants with SC domains in people with SCZ. These findings should stimulate further studies to characterise the genetic underpinning of SC dysfunctions in SCZ.